An Interactive Effect of English Intervention Programme and Medium of Instruction at School of Prospective Teachers on Their Attitude towards English - Ansari, Munnazza Afreen (Modern Perspectives in Language, Literature and Education Vol. 4, 2021)
This paper examines the interaction between an English language communication skills intervention programme and the medium of instruction used in B.Ed. students' schools on their attitudes toward English. For this reason, a 40-hour intervention programme focusing on English language communication skills has been established for B.Ed. students. Students' attitudes about English were assessed using a researcher-created rating scale. The researcher created a personal data sheet for B.Ed. students to collect information about student-teachers' medium of instruction at school. The study included 70 B.Ed. students in each of the experimental and control groups. The experimental group was given an intervention programme, while the control group was not given any. ANCOVA was used to analyse the data. The educational approach was successful in improving B.Ed students' attitudes toward English. The effect size of the intervention programme on attitudes towards English language is 2.21 which is high in magnitude.